2004
DOI: 10.1093/sleep/27.4.784
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Obstructive Sleep Apnea in Pediatric Subjects using Surface Lead Electrocardiogram Features

Abstract: The ability to correctly identify 12 out of 14 cases of OSA (with the 2 false negatives arising from subjects with an apnea-hypopnea index less than 10) indicates that the automated apnea classification system outlined may have clinical utility in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 37 publications
1
58
1
6
Order By: Relevance
“…However, they did not present other measures of accuracy and did not publish raw data to allow calculation of these measures. The discriminant analysis classification system by SHOULDICE et al [47] showed 0.86 sensitivity and 0.82 specificity. However, the test set was small and results were not prospectively confirmed in a larger group of children.…”
Section: Sleep-related Disorders Ms Urschitz Et Almentioning
confidence: 98%
See 1 more Smart Citation
“…However, they did not present other measures of accuracy and did not publish raw data to allow calculation of these measures. The discriminant analysis classification system by SHOULDICE et al [47] showed 0.86 sensitivity and 0.82 specificity. However, the test set was small and results were not prospectively confirmed in a larger group of children.…”
Section: Sleep-related Disorders Ms Urschitz Et Almentioning
confidence: 98%
“…Prediction models are often used in adults to: 1) exclude a diagnosis of OSA when the probability is low so that no further testing is required; 2) establish an a priori probability before considering the use of a diagnostic method other than polysomnography; and 3) prioritise patients needing polysomnography according to the probability that they will have a positive result [45]. Four prediction models for paediatric SDB have been published [46][47][48][49]. They combined several data sources (i.e.…”
Section: Sleep-related Disorders Ms Urschitz Et Almentioning
confidence: 99%
“…Figure 5 demonstrates that SRR index has high accuracy than all compared methods for examining OSA events. The accuracy of single lead approach [19], TVAM (Time-Varying Autoregressive Model) [20], LHR index, sleepAp …”
Section: Correlation Of Srr and Lhr With Ahi And Rdimentioning
confidence: 99%
“…Several techniques incorporate bio-signal based parameters to analyze OSA instead of utilizing traditional PSG method [13][14][15][16][17][18]. ECG signal is a mainly noteworthy signal type to study since it sanctions physiological demonstration of OSA events and is suitable to record using wearable sensors [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…13 All the patients with adenotonsillar hyperplasia who fail to respond to conservative management were subjected to adeno-tonsillectomy surgery.…”
Section: -11mentioning
confidence: 99%